Wrongful refusal to enforce an award and liability before the ECtHR (BTS v. Slovakia) - Vázquez García, Inés; Puig-Samper Naranjo, Inés; Lana Arceiz, Víctor Javier (CUADERNOS DE DERECHO TRANSNACIONAL, 2025)
A detailed analysis of the arbitration case between BTS and Slovakia is presented, focusing on the enforcement of an ICC arbitral award. The dispute arose out of the privatisation of Bratislava Airport and the subsequent termination of the sale and purchase agreement by the Slovak State Agency for the Privatisation of Assets. BTS initiated arbitration proceedings in 2010, which resulted in a favourable award in 2012. However, enforcement of the award in Slovakia was refused by the national courts on the grounds that there was no valid arbitration agreement and that it was contrary to public policy. BTS brought the case to the European Court of Human Rights (ECHR), alleging violations of its right to property and to a fair trial. The ECHR concluded that the refusal to enforce the award constituted an unlawful interference with BTS’s property in violation of art. 1 of Protocol 1 to the European Convention on Human Rights.